The performance of directional flooding routing protocol for underwater sensor networks - Idrus, Nur Asfarina (2015)
The specific characteristic of underwater environment introduces new challenges for the networking protocols. Underwater Wireless Sensor Networks (UWSN) and terrestrial Wireless Sensor Networks (WSN) share some common properties but their differences too. These differences necessitate specialized new protocols for successful underwater communication. In this thesis, a specialized architecture for underwater sensor networks (UWSNs) is proposed and evaluated. Simulation experiments have been carrying out to analyze the suitability of various protocols for the sub aquatic transmission medium, whether in freshwater or seawater. Additionally various scheduling techniques maybe applied to the architecture in order to study their performances. Furthermore, for a given the harsh conditions of the underwater medium, different retransmission methods are combined with the scheduling techniques. The goal of this thesis is to produce simulation results that would illustrate the performances of the proposed protocol for a given metric such as end-to-end delay, packet delivery ratio and energy consumption. From the results, some protocols can be very suitable for the underwater medium.